Purchase Decisions: The Mediating Role Of Brand Image And Moderating Role Of Consumer References In Yamaha's At-LPM Segment In West Java - Eko Wahono; Lili Karmela Fitriani; Odang Supriatna (CV Putra Publisher, 2026)
Intensifying competition in Indonesia's Automatic Low Premium Model (AT-LPM) motorcycle segment—where Honda's BeAT has consistently outsold Yamaha's Gear—has prompted strategic imperatives around digital engagement and customer relationship management. This study examines how digital marketing and relationship marketing shape consumer purchase decisions, mediated by brand image and moderated by consumer references, among Yamaha AT-LPM consumers at Arista Yamaha dealerships across West Java. A quantitative survey design was employed, with data gathered from 265 respondents selected via proportional probability sampling based on Slovin's formula (e = 5%). Structured questionnaires on a five-point Likert scale operationalized five latent constructs. Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4, with 5,000-resample bootstrapping, was used for hypothesis testing. Outer model results confirmed adequate convergent validity (AVE > 0.50), composite reliability (CR > 0.70), and discriminant validity (HTMT < 0.85). Inner model results show: digital marketing positively affects brand image (β = 0.512; t = 8.393; p < 0.001) and purchase decisions (β = 0.214; t = 3.963; p < 0.001); relationship marketing positively affects brand image (β = 0.401; t = 6.365; p < 0.001) and purchase decisions (β = 0.289; t = 4.898; p < 0.001); brand image significantly influences purchase decisions (β = 0.421; t = 6.284; p < 0.001) and fully mediates the paths from both digital marketing (indirect β = 0.215; p = 0.002) and relationship marketing (indirect β = 0.169; p = 0.004); and consumer references positively moderate the brand image–purchase decision relationship (β = 0.167; t = 3.408; p < 0.001). The R² for brand image is 0.614 and for purchase decisions is 0.721. These findings offer actionable guidance for Yamaha and its dealer networks to strengthen digital presence, cultivate relational bonds, and leverage social proof to elevate purchase conversion.